Improving vacuum gas nitriding of a Ti-based alloy via surface solid phase transformation. (March 2022) - Jiang, X.J.; Wang, S.Z.; Feng, Z.H.; Qi, H.B.; Fu, H.; Liu, R.P.
Abstract: The traditional surface nitriding technology of titanium alloy usually adopts the temperature above 700 °C to ensure the nitriding effect, but the high temperature will lead to the deterioration of the Matrix structure and reduce the mechanical properties. In this paper, the metastable β phase was formed on the surface of TiZrAl alloy by laser quenching, compared with the 10 μm thick nitrided layer mainly composed of (TiZr)N and α-Ti phases under the traditional process, the thickness and nitrogen content of nitrided layer were increased by the thermodynamic driving force of β→α phase transformation and the kinetic diffusion of phase interface, the effective thickness of nitrided layer was increased to 15 μm via nitriding at 500 °C. the (TiZr)N and α-Ti phases were dominant in the surface layer, and (TiZr)N0.3 and α-Ti phases were dominant in the inner layer, nitriding layer hardness up to 1200HV. In this paper, a novel nitriding technology is used to achieve excellent nitriding effect at low temperature, which has important reference significance for surface nitriding and carburizing of titanium alloys and other alloy materials. Highlights: Phase transformation composite low temperature nitriding technology for titanium alloy. The effective hardening layer of the coating reaches 20 μm and 1200HV. (TiZr)N and (TiZr)N0.3 are main hardening phases.